[Laiškas] / Steinhauzeris (Steinhauser) [Janas Benjaminas], istorikas - R. Borkovskiui. - (:unkn) unknown (My University, 1759)
1 laiškas apie Karpių bylą su LDK paiždininkiu ir jos referavimą LDK pakancleriui.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Steinhäuser, Johann Benjamin, 1692-1767; Borkovskis, R.; Lietuva